Rare case of undifferentiated uterine sarcoma with neuroectodermal differentiation and osteoclast-like giant cells - Chiu-Hsuan Cheng; Borcherng Su; Dah-Ching Ding (Taiwanese Journal of Obstetrics & Gynecology, 2018)
Objective: We describe the first case of a rare undifferentiated uterine sarcoma exhibiting both neuroectodermal differentiation and osteoclast-like giant cells, and elaborate its morphology. Case report: A 54-year-old woman presented with suprapubic pain, frequent urination, and perimenopausal abnormal vaginal bleeding. Computed tomography revealed a large heterogeneous uterine mass and multiple lung nodules. She received a staging surgery. The tumor pathology examination revealed an undifferentiated uterine sarcoma (UUS) with neuroectodermal differentiation and osteoclast-like giant cells (OGCs). The patient was managed with palliative hospice care; however, she died within 1.5 months of diagnosis. Conclusion: UUSs are rare high-grade tumors observed in elderly women. These women typically present with postmenopausal bleeding and extrauterine diseases and have a poor prognosis. Neuroectodermal differentiation in UUSs has a müllerian origin. The presence of OGCs may suggest a poor prognosis; however, further studies are necessary to determine the exact nature of such neoplasms.